Lower serum insulin-like growth factor 1 concentrations in patients with chronic insomnia disorder - Zhang, Yanan; Sun, Qingqing; Li, Huimin; Wang, Dong; Wang, Ying; Wang, Zan (Frontiers in Psychiatry, 2023)
Objectives: Insulin-like growth factor 1 (IGF-1) is a crucial neurotrophin that is produced in the brain and periphery and may play an important role in insomnia and mood disorders. We aimed to analyze its serum concentrations in patients with chronic insomnia disorder (CID). Methods: Patients with CID were enrolled in this study and divided into the CID group (Generalized Anxiety Disorder-7 [GAD-7] score < 10) and the CID with anxiety group (GAD-7 score ≥ 10). Age- and sex-matched healthy volunteers were recruited as controls. The Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality and the GAD-7 and the Patient Health Questionnaire-9 to assess emotional status. All subjects were monitored via polysomnography, and the serum IGF-1 concentrations in their peripheral blood were detected via enzyme-linked immunosorbent assays. Results: We enrolled 65 patients with CID (of whom 35 had anxiety) and 36 controls. The PSQI score and IGF-1 concentration in the CID and CID with anxiety groups were higher than those in the control group. The apparent difference in IGF-1 concentration between the CID and CID with anxiety groups was not statistically significant. The IGF-1 concentration in patients with CID was linearly correlated with the GAD-7 score, PSQI score, and stage 3 non-rapid eye movement (stage N3) time. Conclusion: The serum IGF-1 concentration in patients with CID was lower than that of participants without CID, negatively correlated with anxiety score and sleep quality, and positively correlated with stage N3 time.